Bureaucratic Reforms as Triggers of Experimental Design: KBS and Public Building in Sweden, 1963–74 - Sigge, Erik (Architectural history, 2022)
This article explores the relationship between architecture and public administration at the Swedish National Board of Public Building (Kungl. Byggnadsstyrelsen, or KBS) in the years 1963–74. This government agency, which existed from 1918 to 1993, was in charge of planning, designing, producing and maintaining public service buildings and facilities. During the 1960s, it was subject to a number of major administrative reforms which, by rationalising the organisation’s activities, sought to make both the construction and maintenance of buildings more cost-effective for the taxpayer. These reforms paralleled rationalisation efforts in the field of architectural design, where structural and material efficiency were sought in the adoption of large-scale systems. The administrative reforms thus went beyond the reorganisation of departments and work priorities to permeate all aspects of the agency’s activities. The article presents the architectural activities of KBS as innovative and experimental responses to bureaucratic structures and requirements. Examination of the design and building processes of three projects — the national telecom headquarters in Farsta, the Garnisonen office complex in central Stockholm and Linköping University — uncovers some of the administrative structures deployed at KBS, and the creative and novel architectural solutions triggered by their integration into design and planning practices.